Pain Sensitivity and Recovery From Mild Chronic Sleep Loss - Roehrs, Timothy A. (Associated Professional Sleep Societies, LLC, 2012)
STUDY OBJECTIVES: To determine whether an extended bedtime in sleepy and otherwise healthy volunteers would increase alertness and thereby also reduce pain sensitivity. SETTING: Outpatient with sleep laboratory assessments. PARTICIPANTS AND INTERVENTIONS: Healthy volunteers (n = 18), defined as having an average daily sleep latency on the Multiple Sleep Latency Test (MSLT) < 8 min, were randomized to 4 nights of extended bedtime (10 hr) (EXT) or 4 nights of their diary-reported habitual bedtimes (HAB). On day 1 and day 4 they received a standard MSLT (10:00, 12:00, 14:00, and 16:00 hr) and finger withdrawal latency pain testing to a radiant heat stimulus (10:30 and 14:30 hr). RESULTS: During the four experimental nights the EXT group slept 1.8 hr per night more than the HAB group and average daily sleep latency on the MSLT increased in the EXT group, but not the HAB group. Similarly, finger withdrawal latency was increased (pain sensitivity was reduced) in the EXT group but not the HAB group. The nightly increase in sleep time during the four experimental nights was correlated with the improvement in MSLT, which in turn was correlated with reduced pain sensitivity. CONCLUSIONS: These are the first data to show that an extended bedtime in mildly sleepy healthy adults, which resulted in increased sleep time and reduced sleepiness, reduces pain sensitivity. CITATION: Roehrs TA; Harris E; Randall S; Roth T. Pain sensitivity and recovery from mild chronic sleep loss. SLEEP 2012;35(12):1667-1672.